Impact of examined lymph node number on lymph node status and prognosis in FIGO stage IB-IIA cervical squamous cell carcinoma: A population-based study - Yong, Jiahui; Ding, Baicheng; Dong, Yaqin; Yang, Mingwei (Frontiers in Oncology, 2022)
Objective We aimed to investigate the association of examined lymph node (ELN) number with lymph node status and long-term survival in FIGO stage IB-IIA cervical squamous cell carcinoma(CSCC) and to determine the minimum number of ELN associated with survival improvement. Method Data from the Surveillance, Epidemiology, and End Results Program (SEER) database of FIGO stage IB-IIA CSCC patients undergoing hysterectomy and pelvic lymphadenectomy in 2004-2016 were analyzed to explore the relationship between ELN number and lymph node status and overall survival (OS) by using the multivariable approach. The estimated probability of falsely identifying a patient as node-negative and the hazard ratios (HRs) for each ELN was fitted with a LOWESS smoother, and the structural breakpoints were determined. X-tile software was used to determine the optimal cutoff value for ELNs. Results A total of 2627 patients were analyzed. The optimal cutoff value of the ELN number was identified as 7 based on the results of X-tile software. The structural breakpoints according to the associations between the number of ELNs and the estimated risk of false-negative lymph node dissection and HRs for overall survival were 9 and 8, respectively. The multivariate analysis indicated that ELN number was an independent prognostic factor for OS, both as a continuous or categorical variable. To further explore the effect of more ELNs on survival, another cutoff value of 17 was chosen to compare the survival curves of patients. The multivariate-adjusted COX model showed that patients with ELN<8 had a significantly higher risk of death than those with ELN8-17 (HR=1.447, 95% CI =1.075-1.947, p=0.015), but there was no significant difference in overall survival between patients with ELN>17 and patients with ELN8-17 (HR=0.822, 95%CI =0.665-1.016, p=0.070). Conclusion A sufficient number of ELNs was associated with better long-term survival in FIGO stage IB-IIA CSCC. At least 8 ELNs need to be examined for prognostic stratification. Excessive lymph node dissection (ELN>17) may not confer additional survival benefits.